Basic principles of the national strategy and action plan for biodiversity conservation - KHASHIR, BELLA OLEGOVNA; KHUAZH, OLEGE ZACHIRIEVICH; APSALIAMOVA, SAIDA OLEGOVNA (The journal of contemporary issues in business and government, 2020)
: The national strategy for the conservation of biodiversity in Russia is formulated on the basis of the goals of the strategy formulated as follows, that the conservation of the biodiversity of natural biosystems at a level that ensures their sustainable existence and non-depletion use, this goal was defined as a general direction of movement for the long term and was not limited to any time period. Preservation of the diversity of domesticated and cultivated forms of living organisms and man- made ecologically balanced natural and cultural complexes at a level that ensures the development of an effective economy and the formation of an optimal environment for human life. At the same time, the conservation of biodiversity meant a set of active actions aimed at achieving the goal of the strategy and including both direct measures for the conservation, restoration and sustainable use of biodiversity, and the application of the socio-economic mechanisms described in the strategy that determine the impact on biodiversity of various population groups and business structures.